Study on the application of the narrow distribution and controlled molecular weight hindered amine lighter stabilizers in poly(butylene succinate). Issue 6 (3rd June 2019) - Liu, Wenjun; Ren, Xiancheng
Abstract: A series of hindered amine light stabilizer (HALS) with controlled molecular weight and narrow distribution was synthesized by reversible addition-fragmentation chain transfer(RAFT) polymerization, and its application in poly (butylene succinate) (PBS) was studied through accelerated aging experiments. The effects of different molecular weight light stabilizers on the degradation of PBS were studied. The aging degree and mechanism of PBS were characterized by attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), differential scanning calorimetry (DSC), scanning electron microscope (SEM) and mechanical properties testing. The extraction experiment was also carried out to study the migration of light stabilizers in PBS. Finally, the biodegradability test was conducted to study the effect of light stabilizers on biodegradation capability. The results showed that the hindered amine light stabilizer with high molecular weight can protect the PBS material to a great extent and reduce the photodegradation degree compared with the one with low molecular weight.